Progress in Flight Physics 2012
DOI: 10.1051/eucass/201203041
|View full text |Cite
|
Sign up to set email alerts
|

Flow structure and turbulence in near fields of circular and noncircular jets

Abstract: Experimental investigation of the turbulent §ow ¦eld of jets emanating from circular and curved-edged noncircular nozzles is conducted using hotwire anemometry. Distributions of the mean velocity vector are obtained by traversing a triple-sensor hot-wire probe at varying streamwise locations downstream of the jet exit plane in a low-speed free-jet facility. Measurements are obtained for a baseline circular nozzle (round jet) and for equilateral triangular and square nozzles. The data are used to compare the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…From a literature survey, previous studies were conducted on the turbulent flow of a jet issuing from differrently shaped nozzles [1][2][3][4][5]. From their results, it was found that the near-field flow of the jet is strongly influenced by the three-dimensional structure dependent on the loss of axisymmetric nature.…”
Section: Introductionmentioning
confidence: 99%
“…From a literature survey, previous studies were conducted on the turbulent flow of a jet issuing from differrently shaped nozzles [1][2][3][4][5]. From their results, it was found that the near-field flow of the jet is strongly influenced by the three-dimensional structure dependent on the loss of axisymmetric nature.…”
Section: Introductionmentioning
confidence: 99%